QUECHUA DIALECTICAL AREAS IN SOUTH OF ANCASH - Solís Fonseca, Gustavo (2002)
Phonologic and morphologic isoglosses let us recognize in the spoken Quechuafrom the south of Ancash, in the territory which belonged to the ancient Bolognesi province, the following more exclusive dialecticformations: Alto Pativilca Quechua, Callejón de Huaylas Quechua, Yaru Quechua, anda Quechua that preserves *le/and *le/. These dialect variants have been identified according to the analysis of the morphologic isoglosses referred to the treatment of the second person marks and the verbal pluralizer; so the following phonologic isoglosses: vocal cluster ofthe sequences lay/, /iy/ and /aw/, "desafricación" of *le/, fronting of *le/and dispalatalization ofll// andlñl. The data allowed us identify Pativilca Riveras a very old dialect border between a Yaru Quechua variety, and another Huaylas kind. In the same manner the linguistic clues indicates the presence ofQuechua elements Cajatambo kind in the south ofAncash, at the other side of the river, is relatively recently; but a/so we can see a retum of Quechua language in the zone ofits primigenia/ matrix Huaylas kind.